ANALISIS SWOT DALAM MENENTUKAN STRATEGI PRODUKSI DAN PEMASARAN SABLON KAOS DI RUMAH TAHANAN NEGARA KELAS 1 SURAKARTA - Mitro Subroto; Ilham Wahidul (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
This study discusses what strategies can be implemented in increasing the production and marketing of screen-printed t-shirts which are carried out as a self-reliance development program in Class 1 prisons in Surakarta. Activities are of course very beneficial for prisoners and these activities can also provide income or income to the detention center as cash or operational funds in improving facilities and infrastructure. Because of this, there is a need for a good strategic analysis so that the work system is sustainable in providing the maximum possible things so that this independence development activity continues and develops rapidly thanks to hard work and clear analysis. The analysis used in this study is the IFAS (Internal Factor Analysis Summary) and EFAS (External Factor Analysis Summary) matrix analysis techniques. The results show that it shows a good strategy in Quarantine I, which means that the strategy applied to improve the quality of production and screen printing activities at the Solo Detention Center is aggressive. Which Aggressive strategy explains that its application is a very profitable situation. The company or organization has opportunities and strengths so that they can take advantage of existing opportunities.